Tonkawa an Indian Language of Texas - Hoijer, Harry (Columbia University Press, 1933)
Examines the history of the Tonkawa, a warlike tribe living in central Texas during most of the 18th and 19th centuries.  Focuses on the language spoken
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: FOREIGN LANGUAGE STUDY / Native American Languages